Comparative Investigation of Inflation in Pakistan and Turkey: Fresh Insights from the Wavelet Coherence Approach - GENÇ, Abdullah Talha; Selçuk, Mervan; KHAN, Shabeer (International Journal of Contemporary Economics and Administrative Sciences, 2023)
Pakistan and Turkey share the same macroeconomic fundamentals as energy dependence, double digits inflation, and tremendous currency depreciation. This paper aims at analyzing the impact that exchange rate, interest rate, and oil price have on the inflation rate in Turkey and Pakistan by using the data period of 2010:M1-2021:M12 and employing the wavelet coherence model. The results show that currency deprecation boosts inflation in both economies. Interest contribution to inflation is more significant in the case of Pakistan compared to Turkey while oil prices only increase inflation in Pakistan compared to turkey. To reduce the impact of currency depreciation on inflation in both nations, an increase in export policy can be implemented, similarly, foreign direct investment can be attracted. Additionally, both nations need to increase the inflow of funds and need to reduce the outflow of funds which will also help them stabilize the currency.